2014
DOI: 10.17152/gefd.15192
|View full text |Cite
|
Sign up to set email alerts
|

5. Sınıf Öğrencilerinin Bilimsel Süreç Becerileri ile Fene Karşı Tutumlarına FeTeMM Etkinliklerinin Etkisi

Abstract: Using a pre-and post-test experimental design, this study investigated the impacts of Science, Technology, Engineering, and Mathematics (STEM) GİRİŞBilgi ve teknoloji çağı olarak adlandırılan çağımızda herkesin kabul ettiği bir gerçek var ki, gelecek neslin yaşayacağı zaman, bizim yaşadığımız zamandan çok farklı olacaktır.Bilgi ve teknolojinin çok hızlı değişmesinden kaynaklanan bu durum, insanların

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
55

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 7 publications
4
56
0
55
Order By: Relevance
“…For instance, Yamak, Bulut and Dundar (2014) reported that working with STEM-based activities helped middle school students improve their science process skills and attitudes towards science. In another study, pursued by Ercan (2014), at the end of a 7-week STEM implementation focusing on Force and Motion, 7 th grade students improved their knowledge about engineering, academic achievement in Force and Motion, and decision making skills.…”
Section: Stem Education Policy and Practicesmentioning
confidence: 99%
“…For instance, Yamak, Bulut and Dundar (2014) reported that working with STEM-based activities helped middle school students improve their science process skills and attitudes towards science. In another study, pursued by Ercan (2014), at the end of a 7-week STEM implementation focusing on Force and Motion, 7 th grade students improved their knowledge about engineering, academic achievement in Force and Motion, and decision making skills.…”
Section: Stem Education Policy and Practicesmentioning
confidence: 99%
“…For example, in a project funded by TUBITAK, 5th grade students (n = 20) used design-based methodology for STEM education, designed solar robots and kaleidoscopes, and created graphs with motion detectors. These activities helped develop positive attitudes towards science (Yamak, Bulut, & Dündar, 2014). In the engineer project students were encouraged to think like engineers by using simple and inexpensive materials (Çavaş, Bulut, Holbrook, & Rannikmae, 2013).…”
Section: Stem Projects and Education Programs In Turkeymentioning
confidence: 99%
“…The projects mainly aim at improving engineering knowledge and skills by using science concepts. For example, studies conducted in the Turkish context revealed that activities that stressed engineering design processes helped teachers and students improve engineering and science processes and skills (Bozkurt, 2014;Çavaş, Bulut, Holbrook, & Rannikmae, 2013;Ercan & Bozkurt, 2013;Yamak, Bulut, & Dündar, 2014).…”
Section: The Conceptualization Of Stem Education In the Turkish Contextmentioning
confidence: 99%
“…Bu bağlamda ulusal ve uluslararası alanda yapılan çalışmalar incelenmiş ve ölçek için gerekli olan ifadeler tespit edilmiştir (Karaçalli ve Korur, 2014;Lou, vd. 2014;Robinson vd, 2014;Rabitoy, Hoffman ve Person, 2015;Ceylan ve Özdilek, 2015;Yamak, Bulut ve Dündar, 2014;Ceylan, 2014;Bennett, Lubben and Hogarth, 2007;Bybee, 2010;Irkıçatal, 2016, Yıldırım ve Altun, 2015Means vd 2016;Chang vd., 2015). Ölçek geliştirilirken temel olarak Buyruk ve Korkmaz, (2016), Siew, Amir ve Chong, (2015), Yıldırım ve Selvi (2015) ile Friday Enstitusü, (2012) tarafından geliştirilmiş ölçeklerden istifade edilmiştir.…”
Section: Veri Toplama Aracıunclassified
“…Dünyada bilim, teknoloji ve ekonomi alanlarında söz sahibi olma noktasında önemli bir eğitim yöntemi olarak görülen FeTeMM'in (Lacey ve Wright, 2009), özellikle son yıllarda Amerika Birleşik Devletleri tarafından üzerinde titizlikle durulmuş ve bu eğitimin sürdürülmesi konusundaki hassasiyete binaen çalışmalar büyük bir hız kazanmıştır. Özellikle alanyazın tarandığında FeTeMM disiplinlerinin bütüncül bir yaklaşımla ele alınmasının öğrencilerin ilgi, tutum, mesleki yönelim gibi özellikleri üzerinde olumlu yönde etkili olduğu sonucuna ulaşan çalışmalara rastlanmaktadır (Schmidt ve Kelter, 2017;Christensen ve Knezek, 2017;Yıldırım ve Selvi, 2017;Gülhan ve Şahin, 2016;Baran, Canbazoğlu Bilici, Mesutoğlu, 2015;Biçer vd, 2015;Gencer, 2015;Yamak, Bulut ve Dündar (2014), Guzey, Harwell ve Moore, 2014;Şahin, Ayar ve Adıgüzel, 2014;Fortus vd., 2004). FeTeMM alanlarına karşı ilgiyi oluşturmak ve geliştirmek, öğrencilerin gelecekte bu alanlarda işgücüne katılmaları açısından oldukça önem taşımaktadır (Knezek vd, 2013).…”
Section: Introductionunclassified